The Potential of the Guitar Craft Industry in Mancasan Village, Baki District in 2021 - Dika Yuliana; Pranichayudha Rohsulina (Universitas Veteran Bangun Nusantara, 2022)
Mancasan Village is one of the villages in Baki District, Sukoharjo Regency. Mancasan Village is one of the villages that is famous for the existence of the guitar industry in the area. The guitar industry is a potential for Mancasan Village because the guitar industry can be one of the successful developments of a region, namely the ability to create job opportunities. The guitar industry in this Mancasan Village classified to in industry small, because on generally every House business this employ around 5-15 employee people, type ownership from business guitar the is individual, using technology which simple and traditional, no have permission business, and the place business which used is the place live or their house alone. The production of guitars in Mancasan Village used to be only through word of mouth or by selling their products directly to music shops. However, along with the times and increasingly sophisticated technology, many guitar craftsmen in Mancasan Village are now marketing their guitar productions online. The potential of the guitar industry in Mancasan Village has an impact on the surrounding community, both the impact on social life and the impact on the economy of the people in Mancasan Village.